ChemInform Abstract: Ambient‐Pressure Synthesis of Two New Vanadium‐Based Calcium Ferrite‐Type Compounds: NaV1.25Ti0.75O4 and NaVSnO4. Issue 41 (October 2015) - Viciu, Liliana; Ryser, Alice; Mensing, Christian; Bos, Jan‐Willem G.
Abstract The title compounds are synthesized (0.5 g scale) at ambient pressure using Na2CO3, V2O3, TiO2, and SnO2 as starting materials (2 d at 650 °C followed by 3 d at 700—750 °C).